Microfluidic device for both active and passive cell separation techniques: A review - Muhammad Asraf Mansor; Muhammad Asyraf Jamrus; Chong Kar Lok; Mohd Ridzuan Ahmad; Michal Petrů; Seyed Saeid Rahimian Koloor (Sensors and Actuators Reports)
Microfluidic separation of particles and cells has been extensively developed in recent years in a wide range of applications of sciences, engineering, and industry. At the same time, this area has been explored within the framework of interdisciplinary study, resulting in several experiments conducted in this field. Due to the heterogeneity of cells, label-free methods that utilize the inherent physical properties of cells to separate, offer more advantages including high throughput, simple design, reduced sample volumes, and low device cost. This paper comprehensively studies the latest progress in microfluidic technology for both active and passive cell separation techniques. In order to limit the extent of this work, our primary emphasis is on six common methods of cell separation: acoustophoresis, dielectrophoresis, magnetophoresis, inertial, pinched flow fractionation (PFF), and deterministic lateral displacement (DLD). We elaborate on the efficiency, throughput rate, and clogging in microfluidic devices. In addition, the advantages and limitations of both microfluidics devices were discussed.